How the electron-deficient Cp ligand facilitates Rh-catalyzed annulations with alkynes. Issue 4 (10th January 2022) - Gao, Han; Hu, Lingfei; Hu, Yanlei; Lv, Xiangying; Wu, Yan-Bo; Lu, Gang
Abstract : The dominant factors for the Cp X ligand effects (Cp* versus Cp E ) on the reactivity for alkyne insertion into cationic and neutral rhodacycles are identified based on energy decomposition analysis. Abstract : The mechanism and origin of the Cp X ligand effects on Rh-catalyzed annulations with alkynes were investigated using DFT calculations and the approach of energy decomposition analysis (EDA). The results reveal that the alkyne migratory insertion is the rate-determining step for the reactions with both acetanilide and 2-phenyl-2-propanol substrates. The higher reactivities with Cp E than with Cp* are due to the promotion of alkyne insertion. EDA results reveal that the dominant factors for the acceleration effect of Cp E are different depending on the electronic properties of rhodacycle intermediates. The alkyne insertion with the cationic rhodacycle is promoted by Cp E due to the stronger stabilizing electronic interactions, including charge transfer, electrostatics, and polarization, between the cationic rhodacycle and alkyne. For the neutral rhodacycle, the higher reactivity for alkyne insertion with Cp E is because of having smaller destabilizing Pauli repulsion between the occupied Rh d orbitals and the alkyne π orbital. The origins of differences in these stabilizing and destabilizing intermolecular interactions are further identified.